2015
DOI: 10.1111/cccr.12094
|View full text |Cite
|
Sign up to set email alerts
|

Publicity, News Content, and Cultural Debate: The Changing Coverage of Blockbuster Movies in Cultural Journalism

Abstract: This article shows that blockbuster movies are predestined to receive media coverage not only because they are increasingly professionally promoted but also because they carry both "publicist" and media commercial news value. The promotional culture surrounding the blockbuster movie event, including the attention devoted to celebrity actors and directors, attracts media audiences, while the movie itself may stimulate sociocultural debate on film esthetics, art, celebrity culture, and the cultural industries. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Regardless of the terminology, i.e., crusaders, patriots, or cheerleaders, this places cultural journalists in an intermediate position between serving the market and the public interest. Using the cultural coverage of blockbuster movies as a case, Kristensen and From () show that cultural departments may have both commercial and public service incentives for covering such popular culture phenomena in a substantial, critical, and engaging manner. Chong (, p. 11), in her interview‐based study of cultural journalists and book critics, shows that “their goal for writing reviews was not to sell books but to inform the general public about new books as part of a broader cultural conversation.” Accordingly, scholars often point to cultural journalists performing the role of cultural intermediary or mediator between cultural producers and cultural citizen‐consumers, thus turning to theories from cultural sociology to explain the distinct role conceptions and performances of cultural journalists (e.g., Hovden & Knapskog, ; Jaakkola, ; Kristensen, ; Kristensen & From, ).…”
Section: The Journalism Culture Of Cultural Journalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the terminology, i.e., crusaders, patriots, or cheerleaders, this places cultural journalists in an intermediate position between serving the market and the public interest. Using the cultural coverage of blockbuster movies as a case, Kristensen and From () show that cultural departments may have both commercial and public service incentives for covering such popular culture phenomena in a substantial, critical, and engaging manner. Chong (, p. 11), in her interview‐based study of cultural journalists and book critics, shows that “their goal for writing reviews was not to sell books but to inform the general public about new books as part of a broader cultural conversation.” Accordingly, scholars often point to cultural journalists performing the role of cultural intermediary or mediator between cultural producers and cultural citizen‐consumers, thus turning to theories from cultural sociology to explain the distinct role conceptions and performances of cultural journalists (e.g., Hovden & Knapskog, ; Jaakkola, ; Kristensen, ; Kristensen & From, ).…”
Section: The Journalism Culture Of Cultural Journalismmentioning
confidence: 99%
“…Regardless of the terminology, i.e., crusaders, patriots, or cheerleaders, this places cultural journalists in an intermediate position between serving the market and the public interest. Using the cultural coverage of blockbuster movies as a case, Kristensen and From (2015c) show that cultural departments may have both commercial and public service incentives for covering such popular culture phenomena in a substantial, critical, and engaging manner. Chong (2017, p. 11), in her interview-based study of cultural journalists and book critics, shows that "their goal for writing reviews was not to sell books but to inform the general public about new books as part of a broader cultural conversation."…”
Section: Institutional Rolesmentioning
confidence: 99%
“…Empirical research has shown that cultural journalists perceive themselves as better educated than other journalists (e.g., Harries & Wahl-Jorgensen, 2007;Hovden & Knapskog, 2015), and they do, in fact, have more or a higher level of education than other types of journalists (Hovden & Kristensen, 2018). Th is has provided them with a mindset that focuses on aesthetic norms and values rather than news values, suggesting that cultural journalists tend to have one leg in academia and another in journalism (Kristensen & From, 2015b). Th is guides their journalistic practices but potentially also their use of social media.…”
Section: Th Eory: Th E Specialised Practices Of Cultural Journalistsmentioning
confidence: 99%
“…Shoemaker, Vos, and Reese 2009). This gatekeeping role is especially important at a time of cultural over-supply, when cultural editors and journalists have to select crudely from the increasingly vast stream of press releases for cultural products and events flowing to their desk (Kristensen and From 2015b;Thompson 2007). While this gatekeeping may thus be influenced by various types of information subsides (Gandy 1982), it may itself influence which cultural products gain broader attention in the cultural public sphere and among cultural consumers-and which are ignored or only picked up by niche publics.…”
Section: Theoretical Framework: Cultural Journalists As "Mediators" Imentioning
confidence: 99%